Applications of the Anaerobic Speed Reserve to Elite 800m Running - Sandford, Gareth (Auckland University of Technology, 2018)
Middle-distance running events (800 and 1500m) require a unique interplay of aerobic and anaerobic energetics, meaning athletes with diverse profiles may have an opportunity to win the race. Historically, research of middle-distance running has centred on the aerobic determinants of performance. Preparatory training approaches to meet these demands have naturally followed. Modern-day international middle-distance standards and depth are becoming increasingly competitive. Within a race, there are tactical moments that differentiate medal outcomes, which are typically underpinned by surges. These moments are supported by high levels of aerobic metabolism, yet potentially concurrent anaerobic, neuromuscular and mechanical characteristics. The anaerobic speed reserve (ASR) represents the speed range an athlete possesses from their velocity at V̇O2max (vV̇O2max) to their maximal sprint speed (MSS). The degree to which the ASR is required within middle-distance events is yet to be investigated. Therefore, an overarching aim of my thesis was to explore the tactical behaviours that differentiate World and Olympic medallists over 800m in the modern era and to analyse the potential importance of the ASR as it relates to these critical moments. To address these aims, the following studies were conducted. Study 1 assessed the evolution of tactical behaviour in the men’s 800m at Olympic Games and World Championships in the modern competition era (2000-2016). Study 2 evaluated the tools currently available to measure the anaerobic qualities underpinning modern day tactics found in study 1. Following the findings of studies 1 and 2, the ASR was determined as the most reliable and practical measure for field application. Study 3, through theoretical modelling, determined whether ASR differences existed between and within middle-distance event groups. To directly address these findings, study 4 involved travel to locations around the world to test elite participants to determine the relationship between ASR and elite 800m performance and further understanding of 800m profile variability. Study 5 aimed to contextualise application of the ASR construct to 800m running, specifically by focusing on the neuromuscular and mechanical determinants of ASR. Study 6 offered sample training data from elite male 800m runners, providing insight into how coaches might apply knowledge of ASR to the different 800m sub-groups identified in study 4. In study 7, it was important to validate the vV̇O2max prediction equation I used in study 4 based on a runner’s 1500m race performance; this variable was instrumental in calculating the ASR construct. Collectively these studies showed: 1) faster sector speed demands than in previous eras of 800m running for Olympic and world medallists, 2) that ASR, as a function of MSS, seems to differentiate faster 800m performers in an elite population, 3) that ASR is a key component of 800m running performance, with additional application for surging in 1500m-10,000m 4) that ASR is a useful tool for categorizing runners into one of three distinct athlete sub-groups (400-800m speed types, 800m specialists and 800-1500m endurance specialists), which may assist coaches to individualise their training approach, and 5) mechanical efficiency of middle-distance runners may be a critical factor limiting surge capability.
Keywords: Maximal Aerobic Speed; Maximal Sprint Speed; Middle Distance Running; Training Science